Video-assisted thoracoscopic surgery for intrathoracic first rib resection in thoracic outlet syndrome - Hwang, Jinwook; Min, Byung-Ju; Jo, Won-Min; Shin, Jae Seung (Journal of Thoracic Disease, 2017)
Background: First rib resection is a surgical treatment for decompressing the neurovascular structures in thoracic outlet syndrome (TOS). Historically, extrathoracic approaches have used a posterior, supraclavicular, or transaxillary incision to remove the first rib. In this report, we demonstrate video-assisted thoracoscopic surgery for intrathoracic first rib resection (VATS-IFRR). Methods: Between 2009 and 2014, eight patients underwent VATS-IFRR for TOS. Surgery was performed through two 5-mm ports and one 10-mm port. Endoscopic graspers, a hook-type electrocautery probe, a long peapod intervertebral disc rongeur, and Kerrison punches were used. The types of disease, operative times, chest tube indwelling days, lengths of hospital stay after operation, perioperative complications, postoperative pain scale ratings, and postoperative symptom recurrence rates at provocation tests were reviewed. The surgical outcomes were compared to published outcomes of extrathoracic approaches and other VATS approaches. Results: The eight patients (3 right ribs, 5 left ribs) exhibited neurogenic (1 patient), combined type (2 patients), arterial (4 patients), and venous type (1 patient) TOS. The mean operative time was 190 (range 155-310) minutes. No mortalities or major complications occurred. The mean chest tube indwelling duration was 6 (range 3–10) days, and the mean postoperative hospital stay was 9 (range 4–21) days. The mean immediate postoperative pain numeric rating scale (NRS) score was 2.7/10 (range 2–4). No recurrence was observed during follow-up (median 25.5 months, range 10–64 months) in any patient. Conclusions: VATS-IFRR was safe and had several advantages. Thus, VATS-IFRR is a minimally invasive surgical option suitable for treating selective cases of TOS.